Application of Digitalization Methods in the Study of Anatomy (KIUT Publication, 2025)
The introduction of digital technologies into the study of anatomy is an important step in the development of medical education. Traditional methods, based on the use of anatomical specimens and illustrations, have limited opportunities for repeated study of material and the development of spatial thinking. Therefore, the use of 3D modeling, virtual reality (VR), and augmented reality (AR) technologies is becoming increasingly important. Objective: To investigate the application of virtual technologies on the quality of anatomy education among medical faculty students.